Performance Indicators for Maintenance in Geothermal Power Plants - Ari Elísson 1988- (2013)
Reliability is important when operating a geothermal power plant. Maintenance is mainly carried out according to preventive maintenance in order to ensure delivery reliability and durability of expensive assets in the production. Preventive maintenance on the other hand is expensive, and maintenance of geothermal power plants is one of the most costly factors in the operation. In order to reach the available opportunities for optimization in the field, measurements have to be made. Performance indicators can be used to track maintenance performance and manage maintenance activities. They provide managers with the right tools for detecting underperformance in the planning or execution process of maintenance activities. When implemented thoroughly, maintenance performances indicators should as well allow for a means of improving on the shown figures. This Master’s thesis was carried out in cooperation with all the operators of geothermal power plants in Iceland and an assessment was made of the current maintenance performance measurement system. Finally an ideal maintenance performance measurement system is presented and a comparison made between the organizations’ current procedures and the ideal model. Viðhald jarðvarmavirkjana er einn umfangsmesti einstaki þáttur í rekstri þeirra, en til þess að tryggja afhendingaröryggi og endingu á dýrum tækjabúnaði er viðhaldi að miklu leiti sinnt með fyrirbyggjandi aðferðum. Skilvirk stjórnun og framkvæmd viðhaldsaðgerða getur því haft mikil rekstrarleg áhrif hjá fyrirtækjunum, en möguleika til úrbóta á því sviði má finna með því að fylgjast með og greina skilvirkni viðhaldsaðgerðanna. Til þess þarf að notast við svokallaða árangursvísa (e. performance indicators) en þeir geta gefið stjórnendum og öðrum sem koma að viðhaldsmálum skýra mynd af stöðu mála hverju sinni. Þannig fá þeir í hendur upplýsingar sem nýta má til þess að bregðast við þegar afköst falla undir væntingamörk. Verkefnið var unnið í samvinnu við rekstraraðila allra jarðvarmavera á Íslandi og mat lagt á ...